Author Response: Frequency of Asymptomatic Optic Nerve Enhancement in a Large Retrospective Cohort of Patients With Aquaporin-4+ NMOSD. (7th February 2023) - Chen, John; Shah, Shailee
Abstract : We thank Dr. Cao and colleagues for raising several interesting points regarding our article. 1 We agree that recurrent optic neuritis (ON) cannot be definitively ruled out. However, patients' examinations at the time of scans did not reveal clinical evidence of ON. Long-term visual acuity was similar between patients with and without interattack enhancement, and the impact of acute therapeutics on asymptomatic lesions in neuromyelitis optica spectrum disorder is unknown. 1 Therefore, we do not feel that acute intervention is entirely justified.